Effects of nano silica on the properties of cement-based materials: A comprehensive review. (3rd May 2021) - Yang, Haibin; Monasterio, Manuel; Zheng, Dapeng; Cui, Hongzhi; Tang, Waiching; Bao, Xiaohua; Chen, Xiangsheng
Highlights: The influence of NS on fresh properties and hydration characteristic of CBM has been reviewed. Incorporation of NS can significantly enhance the mechanical strengths and durability of CBM. There are three main reasons for the performance improvement of CBM with NS. The addition of NS modified the microstructure and micromechanical strength of C-S-H. Abstract: Nowadays, many nanomaterials such as graphene oxide (GO), carbon nanotubes (CNTs), nano silica (NS) etc. have been introduced to improve the microstructures and performances of cement-based materials (CBM). Compared with other nanomaterials, NS has attracted much attention because of its pozzolanic reaction with calcium hydroxide (CH) to form calcium-silicate-hydrate (C-S-H) gel. Although several review papers have been published, the breadth and depth of literature coverage on NS and its effects on CBM is insufficient. This paper is aimed to keep researchers abreast of the latest research in the field. In particular, the influence of NS on CBM properties including workability, setting time, hydration characteristic, calcium leaching, porosity, mechanical strengths, and durability is critically reviewed. It is believed that this review paper will not only arouse new ideas to promote practical application of NS in construction materials but also provide some constructive guidance for similar research in the future.